2023
DOI: 10.1186/s12872-023-03207-w
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C19 loss-of-function is associated with increased risk of hypertension in a Hakka population: a case-control study

Abstract: Background Genetic factors have a certain proportion in the risk factors of hypertension. The purpose was to investigate the relationship of cytochrome P450 2C19 (CYP2C19) polymorphisms with hypertension in Hakka population. Methods The study included 1,872 hypertensive patients and 1,110 controls. The genotypes of CYP2C19 rs4244285 and rs4986893 of all individuals were detected and analyzed. Results T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…It has been reported that rs1057910 genotype of CYP2C9 was related to increased risk of adenoma recurrence (aRR = 1.47, 95% CI: 1.19–1.83) [ 39 ], or developing sporadic colorectal carcinoma (aOR = 2.77, 95% CI: 1.1653–4.643) [ 40 ]. In addition, for the two common polymorphic loci rs12248560 and rs4244285 of CYP2C19 , the genotype of rs12248560 was associated with decreased breast cancer risk (aOR = 0.77, 95% CI: 0.65–0.93) [ 41 ], while rs4244285 polymorphism was related to higher risk of epilepsy (aOR = 4.24, 95% CI: 2.52–7.15) [ 42 ], long-term ischemic stroke events (hazard ratio: 1.64, 95% CI: 1.06–2.53) [ 43 ], hypertension (aOR = 2.433, 95% CI: 1.797–3.293) [ 44 ]. Meanwhile, several studies have observed that CYP2C9 rs1057910 polymorphism was associated with increased risk for adenoma recurrence (aRR = 1.47, 95% CI 1.19–1.83) [ 39 ], or developing sporadic colorectal carcinoma (aOR = 2.589, 95% CI: 1.549–4.330) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that rs1057910 genotype of CYP2C9 was related to increased risk of adenoma recurrence (aRR = 1.47, 95% CI: 1.19–1.83) [ 39 ], or developing sporadic colorectal carcinoma (aOR = 2.77, 95% CI: 1.1653–4.643) [ 40 ]. In addition, for the two common polymorphic loci rs12248560 and rs4244285 of CYP2C19 , the genotype of rs12248560 was associated with decreased breast cancer risk (aOR = 0.77, 95% CI: 0.65–0.93) [ 41 ], while rs4244285 polymorphism was related to higher risk of epilepsy (aOR = 4.24, 95% CI: 2.52–7.15) [ 42 ], long-term ischemic stroke events (hazard ratio: 1.64, 95% CI: 1.06–2.53) [ 43 ], hypertension (aOR = 2.433, 95% CI: 1.797–3.293) [ 44 ]. Meanwhile, several studies have observed that CYP2C9 rs1057910 polymorphism was associated with increased risk for adenoma recurrence (aRR = 1.47, 95% CI 1.19–1.83) [ 39 ], or developing sporadic colorectal carcinoma (aOR = 2.589, 95% CI: 1.549–4.330) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was extracted with magnetic bead method (BioTeke, Wuxi, China) according to the recommended protocol. Twenty SNPs in the UGT1A7 , UGT2B7 , UGT2B15 , CYP2C19 , CYP2C9 were selected based on the following principal criteria: (1) an association with diseases in previous studies or the metabolic level of phthalates [ 28 44 ], (2) a minor allele frequency > 0.05 in Han Chinese. In total, 20 SNPs were selected.…”
Section: Methodsmentioning
confidence: 99%
“…This CYP2C family member catalyzes the metabolism of the arachidonic acid to endothelium-derived hyperpolarizing factor (EDHF), which causes blood vessel relaxation, including the coronary arteries [44]. The defective production of EDHF (due to CYP2C19 gene variants) can cause renal dysfunction and CVD [44]. In addition, the reactions catalyzed by CYP2C generate ROS in coronary arteries [44].…”
Section: Discussionmentioning
confidence: 99%
“…CYP2C19 variants were detected by CYP2C19 genotyping kit (BaiO Technology Co., Ltd, Shanghai, China) with PCR-gene chip method. 37 The specific detection steps are carried out by referring to the method published by our colleagues before. 37…”
Section: Genetic Analysismentioning
confidence: 99%
“…37 The specific detection steps are carried out by referring to the method published by our colleagues before. 37…”
Section: Genetic Analysismentioning
confidence: 99%